LITERARY AND AESTHETIC INTERPRETATION OF THE IMAGE OF A TEENAGER IN ENGLISH LITERATURE - Kasimova Yulduz Malikovna (Bright Mind Publishing, 2025)
This article examines the literary and aesthetic portrayal of the teenager in English literature, with a focus on how adolescence is represented as a period of emotional, psychological, and moral transformation. Drawing on selected works from the 20th and 21st centuries, the study explores how authors construct the image of the adolescent to reflect broader social, cultural, and philosophical concerns. Through character analysis, thematic exploration, and aesthetic evaluation, the article highlights the complexity of teenage characters as both individuals and symbolic figures within literary narratives. The study also considers how literary techniques—such as narrative voice, symbolism, and psychological realism—are used to convey the inner world of teenagers and their struggle for identity, independence, and meaning. Ultimately, the article argues that the literary image of the teenager serves as a powerful lens through which authors critique social norms, explore human development, and reflect on the universal experience of growing up.
Keywords: Adolescence, English literature, teenager image, literary interpretation, aesthetic analysis, identity, psychological development, narrative voice, symbolism, coming-of-age.